From “General Public” to “Beneficiary Representative”: Reconstructing Environmental Social Organizations’ Right to Participate in Environmental Affairs Based on Public Trust Theory - Qing Yu (Economics, Law and Policy, 2026)
The procedural environmental participation rights of environmental non-governmental organizations (hereinafter “ENGOs”) face the predicament of ambiguous subject positioning and procedural rights erosion under the current positive law framework. The public participation rights allocation framework centered on “interest nexus” proves inadequate to address the public interest representation function of ENGOs in environmental governance. This Article introduces the Public Trust Doctrine to reposition ENGOs as “beneficiary representatives” within the “settlor-trustee-beneficiary” tripartite structure, while distinguishing between “expressive rights” and “representative rights” as two categories of procedural entitlements. Based upon the principle of functional appropriateness and legal fiction, the procedural rights of ENGOs are hereby justified. Accordingly, across three dimensions—namely, environmental information access rights, decision-making participation rights, and supervisory rights—this Article constructs a differentiated rights framework that effects a transition from expressive rights to representative rights. This interpretive approach overcomes the structural deficiencies of the interest nexus theory and furnishes a theoretical reference for improving the multi-stakeholder environmental co-governance system.